Optimalisasi Teknologi dan Strategi Pemasaran Digital dalam Meningkatkan Daya Saing UMKM Bakpia Wong Yogyakarta - M. Masrukhan; Riska Khajiyah Isnaini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the optimization of technology and digital marketing strategies in enhancing the competitiveness of Bakpia Wong Yogyakarta SMEs. Using a qualitative descriptive approach, the research explores the application of technology in production processes, such as modern machinery and production management systems, as well as digital marketing strategies through social media, e-commerce, and SEO. The findings reveal that technology utilization increases production efficiency by up to 30%, while digital marketing via online platforms boosts sales by 40%. However, challenges such as limited skilled human resources and digital infrastructure remain significant. This study recommends investing in human resource training, developing more integrated digital strategies, and product innovation to strengthen the competitiveness of SMEs in the digital era.